Has psychopharmacology got a future? - Cowen, P (2011)
Fifty years ago pharmacological discoveries transformed psychiatry but progress since then has been relatively slow and there is unease about the role of industry. Despite this, the possibilities of pharmacological treatment have improved in recent years but exploiting developments for the benefit of patients requires psychotherapeutic skill as well as a high level of scientific knowledge.